Modulation strategy to operate the dual active bridge DC-DC converter under soft-switching in the whole operating range - Oggier, German Gustavo (2011)
A new modulation strategy that allows operating the dual active bridge (DAB) dc–dc converter under soft switching in the whole operating range is proposed. This strategy is ruled by imposing a certain modulation index in one of the two bridges and a phase shift between the transformer primary and secondary voltages. Moreover, the proposed algorithm reduces the reactive power and thus reducing the converter conduction losses. An experimental prototype was implemented and some experimental results are presented to validate the theoretical analysis. The experimental results reveal that the overall efﬁciency of the DAB topology can be improved up to 20% by implementing the proposed modulation strategy instead of the conventional one.